Activity-dependent endogenous taurine release facilitates excitatory neurotransmission in the neocortical marginal zone of neonatal rats - Qian, Taizhe; Chen, Rongqing; Nakamura, Masato; Furukawa, Tomonori; Kumada, Tatsuro; Akita, Tenpei; Kilb, Werner; Luhmann, Heiko J.; Nakahara, Daiichiro; Fukuda, Atsuo (Frontiers in Cellular Neuroscience, 2014)
In the developing cerebral cortex, the marginal zone (MZ), consisting of early-generated neurons such as Cajal-Retzius cells, plays an important role in cell migration and lamination. There is accumulating evidence of widespread excitatory neurotransmission mediated by γ-aminobutyric acid (GABA) in the MZ. Cajal-Retzius cells express not only GABAA receptors but also α2/β subunits of glycine receptors, and exhibit glycine receptor-mediated depolarization due to high [Cl−]i. However, the physiological roles of glycine receptors and their endogenous agonists during neurotransmission in the MZ are yet to be elucidated. To address this question, we performed optical imaging from the MZ using the voltage-sensitive dye JPW1114 on tangential neocortical slices of neonatal rats. A single electrical stimulus evoked an action-potential-dependent optical signal that spread radially over the MZ. The amplitude of the signal was not affected by glutamate receptor blockers, but was suppressed by either GABAA or glycine receptor antagonists. Combined application of both antagonists nearly abolished the signal. Inhibition of Na+, K+-2Cl− cotransporter by 20 µM bumetanide reduced the signal, indicating that this transporter contributes to excitation. Analysis of the interstitial fluid obtained by microdialysis from tangential neocortical slices with high-performance liquid chromatography revealed that GABA and taurine, but not glycine or glutamate, were released in the MZ in response to the electrical stimulation. The ambient release of taurine was reduced by the addition of a voltage-sensitive Na+ channel blocker. Immunohistochemistry and immunoelectron microscopy indicated that taurine was stored both in Cajal-Retzius and non-Cajal-Retzius cells in the MZ, but was not localized in presynaptic structures. Our results suggest that activity-dependent non-synaptic release of endogenous taurine facilitates excitatory neurotransmission through activation of glycine receptors in the MZ.